Further studies of African Acylophorus Nordmann (Coleoptera: Staphylinidae: Staphylininae) - Lott, Derek A. (Zootaxa, 2012)
Following examination of new material of Acylophorus from sub-Saharan Africa three new species are described: A.janaki sp. n. from South Africa, A. uhligi sp. n. from Zimbabwe, A. acufer sp. n. from Botswana and Namibia. New records are listed for all species examined. Thirty species are now recognised from the region.